Eugène Delacroix and the Image of the Middle Ages in the Romanticism Art at the Turn of 1820’s – 1830’s - Goikhman, Elena G. (Actual Problems of Theory and History of Art, 2013)
The article is dedicated to the works of Eugène Delacroix and the French Romantic painting at the turn of 1820’s – 1830’s, the period of the rise of the romantic movement. The research is based on the description of the characteristics of the old master paintings which were the sources for romantics, the study of the special nature of transformation of the old styles and the examination of the ways of the interpretation of literary subjects which inspired romantic painters.
Keywords: Eugène Delacroix; Romanticism; Middle Ages; Rembrandt; Rubens; Veronese; English art; literature; Neoclassicism